2015
DOI: 10.18537/mskn.06.01.07
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de genotipos del papiloma virus humano en mujeres de la provincia del Azuay, Ecuador

Abstract: RESUMEN Los principales objetivos de la investigación fueron detectar en función con la edad, la prevalencia de los genotipos de alto y bajo riesgo oncogénico de virus del papiloma humano (VPH) en muestras cervicales de las mujeres en los catorce cantones de la provincia de Azuay. El proyecto abarcó el diagnóstico histopatológico de las lesiones cervicales intraepiteliales y la relación de los genotipos encontrados, con los factores de riesgo y las vacunas existentes que se utilizan como medida de prevención d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 16 publications
1
8
0
11
Order By: Relevance
“…In Quito, Ecuador, they reported other studies in cytological and/or histologically altered, in which the reported prevalence of HPV was found to be low risk at 67.7% and 86% [ 32 , 33 ]. In the city of Cuenca, in a study of 500 women from the general population, the prevalence of 25.6% of HPV for both high and low risk [ 34 ] was similar to that reported in Santa Elena. Brown et al (2009) found [ 35 ] a prevalence of 24.2%.…”
Section: Discussionsupporting
confidence: 62%
“…In Quito, Ecuador, they reported other studies in cytological and/or histologically altered, in which the reported prevalence of HPV was found to be low risk at 67.7% and 86% [ 32 , 33 ]. In the city of Cuenca, in a study of 500 women from the general population, the prevalence of 25.6% of HPV for both high and low risk [ 34 ] was similar to that reported in Santa Elena. Brown et al (2009) found [ 35 ] a prevalence of 24.2%.…”
Section: Discussionsupporting
confidence: 62%
“…El presente estudio muestra resultados diferentes a los obtenidos en Latinoamérica para mujeres con citología normal. Sin embargo, análisis similares en mujeres indígenas ecuatorianas reportaron porcentajes de infección por VPH hasta de un 30% 19,20 . De la misma forma, la distribución de genotipos puede variar entre países o entre regiones de un mismo país.…”
Section: Resultados Y Discusiónunclassified
“…The objective of this study is to show the prevalence of HPV genotypes in Ecuadorian mestizo women [13], in comparison with other studies at Latin America [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] (see table 3).…”
Section: Introductionmentioning
confidence: 99%